Development of a novel vibro-wind galloping energy harvester with high power density incorporated with a nested bluff-body structure. (1st October 2019) - Sun, Wan; Guo, Feng; Seok, Jongwon
Highlights: A two-DOF vibro-wind galloping energy harvester with a nested structure was developed. High power density is achieved by incorporating the bluff bodies in a nested structure. The inner bluff body plays a significant role in improving the harvester's performance. An aerodynamic interaction between the outer and inner bluff bodies was identified. Abstract: A two degrees of freedom (DOF) vibro-wind galloping energy harvester with a nested structure is proposed to improve wind energy harvesting efficiency. Unlike traditional wind energy harvesters configured in a single bluff body-beam structure, the proposed system comprises outer and inner square cross-sectional bluff bodies in tandem, connected with elastic cantilevered beams to allow separate oscillations. The generated power performance of a conventional single-DOF wind galloping energy harvester and the proposed system is compared through wind tunnel tests. Aerodynamic interactions between the two oscillating bluff bodies are analyzed by varying the gap distances and the coupling mechanism is determined by analyzing their power spectral density (PSD). Experimental results show that the outer bluff body has a dominant influence on the inner bluff body at low wind speed, which is a secondary cause of inner body vibration after the plain galloping directly induced by the incoming wind. The proposed system exhibits excellent performance with a significant power density increase of 27.8%. Moreover, the interference effects between the two bluff bodies can be reinforced by reducing their gap distance. We conclude that the inner bluff body plays a key role in enhancing output power, specifically at relatively high wind speed.